Kesiapan Apoteker dalam Memberikan Layanan Medication Therapy Management - Heni Lutfiyati; Prasojo Pribadi; Setiyo Budi Santoso (STIKES MUHAMMADIYAH KLATEN, 2019)
Optimizing the implementation of the referral program is one of BPJS 'top programs. BPJS Health implements a referral program based on Medication Therapy Management. Medication therapy management interventions can reduce the frequency of drug-related problems, including non-compliance, and reduce health care costs. The purpose of this study was to evaluate the readiness of pharmacists in providing medication therapy management services This research uses a descriptive method by using a questionnaire as an instrument for data retrieval. The sampling technique is convenience sampling. The population is pharmacists who practice pharmaceutical services and are willing to fill out questionnaires. The result most pharmacists feel they have enough clinical knowledge and experience to provide MTM services. There are still many pharmacist workplaces (Puskesmas, Pharmacies and hospitals) that have not yet prepared to provide MTM services. Pharmacists think they have a desire to provide MTM services and have sufficient access to information in designing appropriate MTM services and pharmacists should be involved in providing MTM services. The obstacles faced by pharmacists in providing MTM services are insufficient time, insufficient human resources, limited space, limited information regarding MTM services, and the costs needed to implement MTM. Pharmacists are willing to provide Medication Therapy Management services but many obstacles remain. Training is needed so that pharmacists become more confident in providing clinical services